Calcipotriol cream in childhood psoriasis - Pauluzzi, P... (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 1999)
Background. Calcipotriol ointment, a vitamin D3 synthetic derivative, confirmed its efficacy and its high safety when employed in the treatment of adult psoriasis and sometimes in children, too. Cream seems to be the most clinically appropriate choice to treat particularly delicate and easily irritable skins. Methods. Nine enrolled psoriatic children (mean age 10.1 + 4.1 SD years) were treated with calcipotriol cream (50 ug/g) 2 application/dayduring six consecutive weeks. PASI (Psoriasis Area and SeverityIndex) was evaluated at fortnightly visits. Furthermore, routine laboratory parameters were controlled before and at the end of the treatment. Results. Mean PASI was 2.2+0.5 (SEM) at the baseline, and decreased to 0.7+0.5after six weeks of treatment; a 65.9% reduction was seen. Calcipotriol cream showed an excellent safety, as the lack of irritant cutaneous adverse reactions and/or laboratory parameters alterations. Conclusion. Our clinical experience suggests Calcipotriol cream as one of the most important therapeutic choice in psoriasis.
Keywords: Child; Cholecalciferol; Drug therapy; Ointments; Psoriasis; Treatment outcome